Kualitas Tidur Lansia Balai Rehabilitasi Sosial “MANDIRI” Semarang - Khusnul Khasanah; Wahyu Handayani (Jurnal Keperawatan Diponegoro, 2012)
Quality of sleep in a condition in whice a sleep generates freshness and fitness in time to wake up. Quality of sleep is includes quantitative aspects of sleep such as sleep duration, sleep latency and subjective aspects, such as deep sleep and rest. This research was descriptive study, on 97 elderly people who live at the Mandiri Social Rehabilitation Center. The quality of sleep was measured by Pittsburgh Sleep Quality Index (PSQI). Study findings shown that  29 respondents (29.9%) had a good sleep quality and 68 respondents (70.1%) had poor sleep quality. The results of this study obtained data that the elderly sleep at the Mandiri Social Rehabilitation Center, it can be concluded that overall sleep quality of elderly poor. These results can be used as an illustration for nurses to be able to utilize the data in this study so they can perform nursing care on elderly related to the needs of rest and sleep, for example, they can examine the causes of poor sleep quality in elderly, daily activities, bedtime ritual they used